Exploring Contextual Factors Shaping Internal Audit’s Engagement in Sustainability Practices: A Semi-Systematic Literature Review - Ivana BARIŠIĆ (Communications of International Proceedings, 2025)
Sustainability has become a key element of modern business, and with recent regulations, particularly at the European Union level, reporting on sustainability is gaining increasing importance. For sustainability information to be relevant, reliable, credible, and timely, internal controls over sustainability reporting and their effectiveness become a key issue for management structures. Internal audit is becoming an indispensable partner in ensuring the reliability of sustainability information, both in the public and private sectors. However, its actual involvement varies considerably across organisations, prompting a need to understand better the contextual factors that influence its role. This paper aims to analyse recent research regarding the factors related to internal audit engagement in sustainability reporting. A semi-systematic literature review was conducted of recent sources indexed in Scopus combined with thematic analysis. The analysis findings indicate the existence of various factors related to the involvement of internal audits in sustainability processes and sustainability reporting. They are related to relationships with key stakeholders, as well as those related to the internal audit function itself, such as a risk-based approach to internal audit, characteristics like size and effectiveness, and the use of information technology in internal audit. The identified themes indicate that the involvement of internal audit in sustainability processes must be viewed multidimensionally to consider factors from different perspectives that influence the role of internal audit in sustainability processes while also enhancing the impact of its work in this context. The study contributes to both academic discourse and professional practice by offering a nuanced understanding of internal audit’s evolving role in the sustainability domain.
Keywords: internal audit; sustainability; contextual factors